EFFECT OF DPPH CONCENTRATION VARIATION ON ANTIOXIDANT ACTIVITY OF EXTRACT OF RASAM FERN LEAF (Dicranopteris linearis) - Henny Nurhasnawati; Risa Supriningrum; Ardani Ardani (UPT Publication and Journal Management, Islamic University of Kalimantan, 2025)
Dicranopteris linearis (rasam fern) is known to contain flavonoid compounds that exhibit significant antioxidant activity. In this study, the antioxidant potential of rasam fern leaf extract was assessed using the DPPH assay at three different concentrations: 30 ppm (P1), 40 ppm (P2), and 50 ppm (P3). Phytochemical screening confirmed the presence of flavonoids, tannins, and saponins in the extract. The IC50 values obtained for each treatment were as follows: P1 = 8.37 ppm, P2 = 12.31 ppm, and P3 = 13.57 ppm, all of which fall within the category of very strong antioxidant activity. Statistical analysis using one-way ANOVA revealed a significant difference in IC50 values among the three DPPH concentrations. These results indicate that variations in DPPH concentration significantly influence the IC50 values, thereby affecting the accuracy and interpretation of antioxidant activity measurements.